Hotter Drought Escalates Tree Cover Declines in Blue Oak Woodlands of California - Dwomoh, Francis K.; Brown, Jesslyn F.; Tollerud, Heather J.; Auch, Roger F. (Frontiers in Climate, 2021)
California has, in recent years, become a hotspot of interannual climatic variability, recording devastating climate-related disturbances with severe impacts on tree resources. Understanding the patterns of tree cover change associated with these events is vital for developing strategies to sustain critical habitats of endemic and threatened vegetation communities. Our main objective was to assess patterns of tree cover change, especially the impacts of the 2012 – 2016 drought within the distribution range of blue oak (Quercus douglasii), an endemic tree species to California with a narrow geographic extent. We utilized multiple, annual land-cover and land-surface change products from the US Geological Survey (USGS) Land Change Monitoring, Assessment and Projection (LCMAP) project along with climate and wildfire datasets to monitor changes in tree cover state and condition and examine their relationships with interannual climate variability during the 1985–2016 study period. Here, we refer to a change in tree cover condition without a land-cover change to another class as “conditional change”. Our results show that the unusual drought of 2012–2016, associated with anomalously high temperatures and vapor pressure deficit, was associated with exceptional spikes in the amount of both fire and non-fire induced tree cover loss and tree cover conditional change, especially in 2015 and 2016. Sudden increases in tree cover loss through medium to high severity fires coincided with exceptionally dry and hot years. By supporting the assessment of both thematic and conditional land-cover change, our study demonstrates the usefulness of the LCMAP products for monitoring the impacts of climatic extremes and disturbance events on vegetation cover over a multi-decadal time span. Our results signify that blue oak woodlands may be vulnerable to extreme climate events and changing wildfire regimes. Here, we present early evidence that frequent droughts associated with climate warming may continue to impact tree cover in this region, while drought interaction with wildfires and the resulting feedbacks may have significant influence as well. Consequently, efforts to conserve the blue oak woodlands, and potentially other vegetation communities in the Western U.S., will need to consider climate risks as well as the potential for climate–fire and vegetation feedbacks.